IGFBP-3/IGFBP-3 Receptor System as an Anti-Tumor and Anti-Metastatic Signaling in Cancer - Qing Cai; Mikhail Dozmorov; Youngman Oh (Cells, 2020)
Insulin-like growth factor binding protein-3 (IGFBP-3) is a p53 tumor suppressor-regulated protein and a major carrier for IGFs in circulation. Among six high-affinity IGFBPs, which are IGFBP-1 through 6, IGFBP-3 is the most extensively investigated IGFBP species with respect to its IGF/IGF-I receptor (IGF-IR)-independent biological actions beyond its endocrine/paracrine/autocrine role in modulating IGF action in cancer. Disruption of IGFBP-3 at transcriptional and post-translational levels has been implicated in the pathophysiology of many different types of cancer including breast, prostate, and lung cancer. Over the past two decades, a wealth of evidence has revealed both tumor suppressing and tumor promoting effects of IGF/IGF-IR-independent actions of IGFBP-3 depending upon cell types, post-translational modifications, and assay methods. However, IGFBP-3′s anti-tumor function has been well accepted due to identification of functional IGFBP-3-interacting proteins, putative receptors, or crosstalk with other signaling cascades. This review mainly focuses on transmembrane protein 219 (TMEM219), which represents a novel IGFBP-3 receptor mediating antitumor effect of IGFBP-3. Furthermore, this review delineates the potential underlying mechanisms involved and the subsequent biological significance, emphasizing the clinical significance of the IGFBP-3/TMEM219 axis in assessing both the diagnosis and the prognosis of cancer as well as the therapeutic potential of TMEM219 agonists for cancer treatment.